Prognostic Value of Sarcopenia for Long-Term Mortality in Extracorporeal Membrane Oxygenation for Acute Respiratory Failure. Issue 4 (April 2020) - Cho, Woo Hyun; Choi, Yoon Young; Byun, Ki Sup; Lee, Seung Eun; Jeon, Doosoo; Kim, Yun Seong; Han, Junhee; Yeo, Hye Ju
Abstract : It is unclear whether sarcopenia is responsible for long-term mortality in patients who require extracorporeal membrane oxygenation (ECMO) for acute respiratory failure. We retrospectively reviewed 127 patients who underwent computed tomography imaging before initiating ECMO from June 2014 to November 2017. The patients were divided into two groups according to the skeletal muscle index (SMI): low SMI (n = 47) and high SMI (n = 80). Mean age was lower in the high SMI group than in the low SMI group (60.2 vs. 53.9 years, p = 0.002). Mean body mass index was higher in the high SMI group than in the low SMI group (21.6 vs. 24.1 kg/m 2, p = 0.001). The mean Charlson comorbidity index (CCI) was lower in the high SMI group than in the low SMI group (3.0 vs. 2.2, p = 0.024). After propensity score matching for age and CCI score, no differences were observed in ECMO weaning success rate or hospital mortality between the two groups. However, the 1 year mortality rate was higher in the low SMI group than in the high SMI group (70.2% vs. 46.8%, p = 0.021). Multivariate analyses showed that renal replacement therapy (odds ratio [OR] 3.99, 95% confidence interval [CI] 1.74–9.13, p = 0.001) and low SMI (OR 5.47, 95% CI 2.31–12.98, p < 0.001) were associated with 1 year mortality. Kaplan–Meier analyses revealed that a low SMI predicted mortality (χ 2 = 13.20, p < 0.001). Sarcopenia predicted worse 1 year mortality in patients who underwent respiratory ECMO. Abstract : Supplemental Digital Content is available in the text.